Improving the return on investment in ports: opportunities in data management. Issue 4 (December 2018) - Kenyon, G.; Goldsmith, M.; Neureuther, B.; Zhou, D.
Abstract Ports provide a critical link in the supply chain by connecting sea, air, and land transport. They provide facilities and services for the transfer, storage, inspection, and control of the goods moving both in and out of a country. Inefficient port management can increase costs considerably and hamper the timeliness of delivery. Many traditional industry techniques fail to capitalize on the global nature of data, thereby omitting the maximum benefit available. The objective of this research is to investigate issues associated with inefficient port operations and suggest new disruptive methods for resolving them. This research proposes to examine the factors of accepted industry practice, data management, and enterprise asset management to help link and streamline operational processes at sea ports. Specifically, we look at the accepted definition of a Port Community System and expand this to a Port Eco-System (PES), a system that includes the addition of interdependent stakeholders. Through the lens of a PES, this research concludes that ports can substantially improve their existing return on investment, by as much as 30% or more, through the streamlining of operational processes.